Florfenicol and Florfenicol Amine Quantification in Bull Serum and Seminal Plasma by a Single Validated UHPLC-MS/MS Method - Anisa Bardhi; Juan E. Romano; Giampiero Pagliuca; Alice Caneschi; Andrea Barbarossa (Veterinary Medicine International)
Florfenicol is a broad-spectrum antibiotic belonging to the amphenicols class that inhibits protein synthesis by binding to bacteria's ribosomal subunits. This drug is commonly used in veterinary medicine to treat bacterial infectious diseases in cattle, swine, poultry, and fish. The proposed method uses a quick protein precipitation with acetonitrile for the extraction of florfenicol and florfenicol amine in serum and seminal plasma, followed by analysis in UHPLC-MS/MS for their simultaneous quantification. A BEH C18 reversed-phase column was chosen for analyte separation, allowing to obtaining sharp and symmetrical peak shapes in a chromatographic run of just 3.5 min under programmed conditions. Two specific transitions were observed for each analyte, and florfenicol-d3 was used as the internal standard. The approach was fully validated in each matrix over ranges suitable for field concentrations of florfenicol and florfenicol amine, showing good linearity during each day of testing (R2 always >0.99). Excellent accuracy and precision were demonstrated, for both analytes, by calculated bias always within ±15% and CV% always below 15% at all QC levels tested. The satisfactory outcomes obtained during recovery, matrix effect, and process efficiency investigations in serum and seminal plasma confirmed the strength of the method for the quantification of target compounds. To our knowledge, this is the first LC-MS/MS-validated approach for the quantification of florfenicol and florfenicol amine in serum and seminal plasma and was successfully applied for the determination of their concentration-time profiles in bulls. This paves the way to understanding the pharmacokinetics of this antibiotic and its active metabolite in bull’s seminal plasma, which will enable the design of more appropriate treatment protocols.